METHODS FOR DETERMINING THE DEGREE OF PREVALENCE OF GUM RECESSION IN PATIENTS OF DIFFERENT AGE GROUPS - Elyor E. Sabirov (Central Asian Journal of Medicine, 2025)
To date, from the total number of periodontal diseases, the gum recession is 10%. Gum recession increases with age: occurs in children from 15% in different manifestations, approaching 90% after 65 years of age. Recession can be the result of a physiological process of aging, as well as progressive inflammation and lesions in periodontal tissues. Varying in shape and depth, this periodontal pathology creates the need for scientists to develop methods and tools that allow them to aesthetically eliminate various forms of this periodontal pathology. Data analysis in the literature shows that the effectiveness of measures to determine the degree of prevalence of gumrecession is determined primarily by identifying the factors that cause gum recession, correctly choosing the treatment criterion used and eliminating observable complications.